Let's expand both expressions step by step to achieve the polynomial in standard form.
First Expression:
\[ (2x^2 - x + 3)(x^2 - 6x + 2) \]
-
Distribute \(2x^2\): \[ 2x^2 \cdot (x^2 - 6x + 2) = 2x^4 - 12x^3 + 4x^2 \]
-
Distribute \(-x\): \[ -x \cdot (x^2 - 6x + 2) = -x^3 + 6x^2 - 2x \]
-
Distribute \(3\): \[ 3 \cdot (x^2 - 6x + 2) = 3x^2 - 18x + 6 \]
Now, combine all terms: \[ (2x^4 - 12x^3 + 4x^2) + (-x^3 + 6x^2 - 2x) + (3x^2 - 18x + 6) \]
Combine like terms:
- \(2x^4\)
- \((-12x^3 - x^3) = -13x^3\)
- \((4x^2 + 6x^2 + 3x^2) = 13x^2\)
- \((-2x - 18x) = -20x\)
- Constant term: \(6\)
Final expression in standard form: \[ 2x^4 - 13x^3 + 13x^2 - 20x + 6 \]
Second Expression:
\[ (x^2 - x - 2)(-x^2 + 3x - 6) \]
-
Distribute \(x^2\): \[ x^2 \cdot (-x^2 + 3x - 6) = -x^4 + 3x^3 - 6x^2 \]
-
Distribute \(-x\): \[ -x \cdot (-x^2 + 3x - 6) = x^3 - 3x^2 + 6x \]
-
Distribute \(-2\): \[ -2 \cdot (-x^2 + 3x - 6) = 2x^2 - 6x + 12 \]
Now, combine all terms: \[ (-x^4 + 3x^3 - 6x^2) + (x^3 - 3x^2 + 6x) + (2x^2 - 6x + 12) \]
Combine like terms:
- \(-x^4\)
- \((3x^3 + x^3) = 4x^3\)
- \((-6x^2 - 3x^2 + 2x^2) = -7x^2\)
- \((6x - 6x) = 0x\)
- Constant term: \(12\)
Final expression in standard form: \[ -x^4 + 4x^3 - 7x^2 + 12 \]
Summary of Results:
-
First Expression: \[ 2x^4 - 13x^3 + 13x^2 - 20x + 6 \]
-
Second Expression: \[ -x^4 + 4x^3 - 7x^2 + 12 \]